Sexual Harassment Reflected In Novel The House On Mango Street: A Feminist Perspective - Yanti, Elga Dwi; Nugroho, Abdillah (UNIVERSITAS PAKUAN, 2024)
This study aims to investigate the underlying themes of sexual harassment in